Quality of work life as perceived by staff nurses and its relation to their turnover intention at critical care units - Essam Ahmed Abdelhakam Ahmed; Magda Abdelhamid Abdelfattah; Safaa Mohamed Abdelrahman (Cairo : Essam Ahmed Abdelhakam Ahmed, 2015)
A high quality of work life (QWL) is essential and critical for hospitals to attract new nurses and retain qualified and motivated workforce. Consequently, hospitals are seeking ways to address the issues of recruitment and retention by achieving a high QWL. The aim of this study was to assess quality of work life as perceived by staff nurses and its relation to their turnover intention at critical care units. A descriptive correlational design was utilized. The study was conducted at 5 critical care units in Minia university Hospital. A convenience sample of (80) staff nurses working in critical care units was used. Two tools were utilized; first tool was a modified Quality of Nursing Work Life (QWL) Questionnaire and the second tool was turnover intention questionnaire. The findings of study indicated that (71.3%) of participants reported that they had average level of quality of working life and as for turnover intention among participants, (75%) of them had the intention to leave the hospital. Finally, a significant negative correlations was found between Quality of work life as perceived by staff nurses and their turnover intention at critical care unit. The study concluded that it is important to promote and maintain quality of work life of nurses for increasing productivity, reducing turnover and improving quality of care. The study recommended that Hospital administrators might be able to improve the level of QWL by increasing nurses{u201F} satisfaction with job security professional recognition, work conditions, work schedule, workload and nursing staffing
Thesis (M.Sc.) - Cairo University - Faculty of Nursing - Department of Nursing Services Administration
Issued also as CD
Keywords: Quality of work life; Staff nurses; Turnover intention